Динаміка морфологічних показників крові у собак за впливу кормових фітодобавок «Фітопанку» та «Гастроациду» - Антоненко, Петро Павлович; Antonenko, Petro; Качалова, Олеся Анатоліївна; Kachalova, Olesya; Приварніков, Костянтин Єдуардович; Privarnіkov, Kostyantin (Дніпропетровський ДАЕУ, 2016)
Наведено дані щодо впливу різних доз кормових фітодобавок “Фітопанку” та “Гастроациду” на загальний стан, морфологічні показники крові собак за профілактики шлунково-кишкових хвороб та хвороб підшлункової залози. Встановлено, що кормові фітодобавки не мають негативного впливу на поведінку, загальний стан шкіри та слизових оболонок тварин, сприяють нормалізації морфологічних показників крові, функції печінки та процесів метаболізму, що зменшує ризик виникнення шлунково-кишкових захворювань та захворювань підшлункової залози у собак. In article data on influence of different doses of the feed phytonutrients of “Fitopank” and “Gastroacid” on the General state, morphological parameters of dogs blood in the prevention of gastrointestinal diseases and pancreas. Phyto-additives have anti-inflammatory, antispasmodic, antibacterial, choleretic, analgesic effect, normalizes gastric secretion, motor function of the gastrointestinal tract, improve digestion, enhance the immune reactivity of the organism and stimulate the regeneration of damaged tissues. The study was performed on dogs older than one year with different species. Dogs of the experimental group orally 30 minutes before feeding asked feed phyto-additives “Fitopank”, and 60 minutes after feeding “Gastroacid” according to the following scheme (0.05 ml/kg - minimum dose), the second experimental group (0.1 ml/kg average), and third experimental group (0.2 ml/ kg – maximum), respectively in 10, 20 and 30 ml. of boiled water cooled to 37 0C for 15 and 30 days. All studies were conducted according to generally accepted methods. Examination of peripheral blood showed that feed phyt-oadditives “Fitopank” and “Gastro-acid” practically do not cause significant changes in hemoglobin levels, hematocrit value, red blood cell count and color index of the blood, and leukogram. Along with the fact that when used in a dose of 0.05 ml/kg after 30 days of using the number of erythrocytes increased from 4,0±0,4, 7,2±0,33. The introduction of a dose of 0.1 ml/kg resulted in increased reticulocytes, and after 30 days twice (8,3±3,3 vs. 4,0±0,43), while in one animal currently recorded in blood samples of 19 of reticulocytes. In applying the drug in a dose of 0.2 ml/kg after 15 days there was an increase in the number of reticulocytes to 6.3±0.3 and after 30 days of a drastic reduction of 0,75±0,01 compared with 4.7±0,26. The number of leukocytes in a dose of 0.1 ml/kg after 15 and 30 days of the experiment decreased to 5.8±0.63 and from 9.1±0,63 and to 4.9±0.22 8,2±0,4. It is established that phyto-additives have no negative impact on the behavior, General condition of the skin and the membranes clinistix animals, contribute to the normalization of morphological blood indices, liver function and metabolism, which reduces the risk of gastrointestinal diseases and pancreas in dogs.
Dynamics of morphological indicators of dogs blood for feed Phytonutrients «Fitopank» and «Gastroacid»
Keywords: кормова фітодобавка “Фітопанк"; phytonutrients «Fitopank»; кормова фітодобавка "Гастроацид"; phytonutrients «Gastroacid»; морфологічні показники крові; morphological parameters of blood; травна система; digestive system; підшлункова залоза собаки; dog's pancreas; превентивні заходи; preventive measures